Faradaic and Capacitive Components of the CNT Electrochemical Responses - Otero, Toribio F.; Martinez, Jose G.; Asaka, Kinji (Frontiers in Materials, 2016)
The nature of the electrochemical responses from carbon nanotubes, capacitive (physical) or Faradaic (chemical, also named p-doping or n-doping) remain controversial. In this chapter the literature is reviewed and discussed trying to elucidate if some of the two processes prevails, how the presence of chemical reactions can be elucidate and which properties, specific from the chemical processes, can be exploited. Different electrochemical responses and theories trying to explain those responses are discussed. The separation and quantification methodologies of the capacitive and Faradaic components involved in some electro-chemical responses from CNTs are presented.